Appraising the impact of activated clay geopolymer as a sustainable geopolymer cement for oilwell applications - Money, Barima; Siti Qurratu’ Aini, Mahat; Gbadamosi, Afeez Olayinka; Modather, Rayan Hassan; Nyah, Francis; Abutu, David; Junin, R.; Nwaichi, Peter Ikechukwu; Agi, Augustine Aja (Society of Petroleum Engineers, 2025)
With growing concerns over global warming, there is a pressing need to replace Portland cement, widely used in the oil and gas industry, due to the significant carbon dioxide (CO2) emissions associated with its production. Geopolymer cement has emerged as a promising alternative due to its environmentally friendly properties and ability to meet the specifications required for oilwells. The use of clay, a naturally sourced material, further enhances the sustainability of this cement, making it a cost-effective option. This study aims to explore the impact of various curing temperatures and hydration times on clay-based geopolymer cement. Two samples were prepared under four different curing temperatures: ambient temperature (23°C), 40°C, 60°C, and 80°C. The most robust samples from each temperature group were then cured at three different hydration times (24, 72, and 120 hours). To assess acid resistance, the samples were submerged in a 3%/12% HF/HCl acid solution for 24 and 72 hours. The results indicated that geopolymer cement exhibited higher compressive strength under elevated temperatures and acidic conditions. Additionally, geopolymer cement demonstrated superior mechanical properties compared to conventional cement. These findings contribute to advancing environmentally sustainable practices in the oilwell well cementing process.